Global, regional and local dimensions of western Saharás protracted decolonization : when a conflict gets old - Ojeda García, Raquel; Fernández-Molina, Irene; Veguilla, Victoria (New York Palgrave, 2017)
This book explores the traces of the passage of time on the protracted and intractable conflict of Western Sahara.
Keywords: Paz; Relaciones internacionales -- Sahara; Sahara -- Situación social